A multi-stage temperature control sintering method for preparing high-density zirconia ceramic plate
Patent Information
- Application Number
- CN202611224645.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种高致密氧化锆陶瓷板的多段控温烧结制备方法,以解决现有单段烧结工艺导致的致密度不足、晶粒异常长大及微观结构不均匀等技术问题
[0026]1、本发明采用四段阶梯式控温烧结制度,将排胶、预烧结、致密化、晶粒调控等过程分段精准控制,有效避免了单段烧结的升温-保温矛盾,使坯体在不同温度区间获得最优的烧结驱动力和扩散传质条件;
Abstract
Description
Technical Field
[0001] This invention belongs to the field of refractory materials technology, specifically relating to a multi-stage temperature-controlled sintering preparation method for high-density zirconia ceramic plates. Background Technology
[0002] The converter slide plate is a key functional component for controlling the slag blocking and flow rate of molten steel. As the core embedded element in the slide plate that directly bears the erosion of molten steel and slag, the density and microstructure uniformity of the zirconia ceramic plate (zirconia plate, zirconia ring) directly determine the service life and safety of the slide plate.
[0003] Currently, the industrial production of zirconia ceramic plates mostly employs a single-stage high-temperature sintering process with one-time kiln loading. This process suffers from the following prominent problems: First, a single heating rate and a single holding platform cannot simultaneously meet the different needs of multiple sintering stages, such as debinding, densification, and grain control, resulting in residual porosity and insufficient density within the green body. Second, excessively long holding times in the high-temperature stage can easily induce abnormal grain growth, leading to a decrease in the material's thermal shock resistance and making it prone to thermal shock cracking and spalling during use. Third, the lack of active control over the atmospheric environment at different sintering stages results in uneven zirconia crystal transformation and stabilizer distribution, affecting the uniformity of the microstructure. These problems severely restrict further improvement in the performance of zirconia ceramic plates for converter slide plates, necessitating the development of a sintering preparation method that can effectively improve density, suppress abnormal grain growth, and improve microstructure uniformity. Summary of the Invention
[0004] The purpose of this invention is to provide a multi-segment temperature-controlled sintering method for preparing high-density zirconia ceramic plates, so as to solve the technical problems such as insufficient density, abnormal grain growth and uneven microstructure caused by the existing single-segment sintering process.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A multi-segment temperature-controlled sintering method for preparing high-density zirconia ceramic plates includes the following steps:
[0007] 1. Raw material preparation: The raw materials are fused magnesium stabilized zirconia powder, monoclinic zirconia ultrafine powder, and magnesia stabilizer; by mass percentage, take 60%~75% fused magnesium stabilized zirconia powder, 20%~35% monoclinic zirconia ultrafine powder, and 2%~5% magnesia stabilizer.
[0008] Add 3-6% binder by weight of the raw material and 1-3% deionized water by weight of the raw material. Use zirconia balls as the grinding medium and ball mill for 6 hours to mix evenly to obtain a slurry.
[0009] 2. Granulation and molding: The slurry obtained in step 1 is spray-granulated to obtain spherical granulated powder with a particle size of 50μm~200μm. Then, the granulated powder is loaded into a mold and isostatically pressed under a pressure of 80MPa~120MPa to obtain a zirconia ceramic slab.
[0010] 3. Green body drying: Place the green body obtained in step 2 in a drying device and dry it at a temperature of 60℃~110℃ for 12h~24h to reduce the moisture content of the green body to below 0.5%;
[0011] 4. Multi-stage temperature-controlled sintering: The green body dried in step 3 is loaded into the sintering furnace and the following sintering process is performed:
[0012] a. First heating stage: Increase the temperature from room temperature to 550℃~600℃ at a rate of 1.5℃ / min~2.5℃ / min, and hold for 1h~2h;
[0013] b. Second heating stage: Heat to 1100℃~1200℃ at a rate of 1.0℃ / min~2.0℃ / min, and hold for 2h~3h;
[0014] c. Third heating stage: Heat to 1450℃~1550℃ at a rate of 1.5℃ / min~2.5℃ / min, and hold for 3h~5h;
[0015] d. Fourth heating stage: Heat to 1680℃~1750℃ at a rate of 0.5℃ / min~1.5℃ / min, hold for 4h~8h, and control the oxygen partial pressure in the furnace at 5%~15% during this stage;
[0016] e. Cooling section: Cool to 800℃~1000℃ at a rate of 2℃ / min~4℃ / min, then allow to cool naturally to room temperature with the furnace to obtain a high-density zirconia ceramic plate.
[0017] Furthermore, in step 1, the particle size D50 of the fused magnesium stabilized zirconia powder is 5μm~15μm, and the particle size D50 of the monoclinic zirconia ultrafine powder is 0.3μm~0.8μm.
[0018] In step 1, the binder is either a polyvinyl alcohol solution or a phenolic resin, and the amount added is 3% to 6% of the total mass of the raw materials.
[0019] In step 4, stage d, the oxygen partial pressure is regulated by introducing a mixture of oxygen and inert gas into the furnace, wherein the inert gas is argon or nitrogen.
[0020] In step 4, stage d, a two-stage heat preservation method is adopted: first, the temperature is kept at 1680℃~1700℃ for 2h~4h, and then the temperature is increased to 1720℃~1750℃ at a rate of 0.5℃ / min~1.0℃ / min and kept for 2h~4h.
[0021] Granulation and molding: The slurry obtained in step 1 is spray-granulated to obtain spherical granulated powder with a particle size of 50μm~200μm; the original particle size D50 of the submicron monoclinic zirconia powder is only 0.3μm~0.8μm, which belongs to the category of ultrafine powder. Due to their small particle size, large specific surface area, and significant van der Waals forces and electrostatic forces between particles, ultrafine powders are prone to agglomeration and "bridging" under natural conditions, resulting in extremely poor powder flowability and making it impossible to uniformly fill the mold cavity by gravity.
[0022] Spray granulation agglomerates dozens or even hundreds of original fine particles into spherical secondary particles with a diameter of 50μm to 200μm, fundamentally altering the macroscopic flow characteristics of the powder. The contact between the spherical particles is point contact, resulting in minimal friction and low rolling resistance, endowing the granulated powder with excellent flowability and filling properties. Testing showed that the flowability index of the granulated powder prepared within this particle size range is 20s / 50g to 30s / 50g, and the loose bulk density reaches 1.30g / cm³ to 1.55g / cm³. During mold filling, the granulated powder can quickly and uniformly fill all corners of the cavity, avoiding filling defects such as localized looseness or bridging voids, laying the foundation for obtaining a green body with uniform density.
[0023] Particle packing density is closely related to particle size distribution. When particles of a single size are packed together, regardless of the arrangement, there is an upper limit to the theoretical maximum packing density (e.g., 74.05% for face-centered cubic packing). To achieve higher packing density, a reasonable particle size distribution is required, allowing smaller particles to fill the gaps between larger particles.
[0024] The spherical granulated powder obtained by spray granulation has a particle size distribution of 50μm~200μm, exhibiting a certain particle size distribution width. The relatively smaller granulated powder particles can fill the gaps between larger particles, forming a good secondary packing structure. Simultaneously, the interior of each granulated powder consists of tightly aggregated submicron-sized zirconia particles with low internal porosity. This dual packing effect of "microscopic density + macroscopic close packing" results in an initial relative density of 58%~65% for the green body, 10%~15% higher than that of traditional mechanical granulation processes. Higher initial packing density means smaller pore volumes to be eliminated during subsequent sintering, shorter inter-particle diffusion distances, and a greater densification driving force, enabling sufficient densification at relatively lower sintering temperatures and effectively reducing sintering energy consumption.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. The present invention adopts a four-stage stepped temperature control sintering system, which precisely controls the processes of debinding, pre-sintering, densification, and grain regulation in stages, effectively avoiding the contradiction between heating and holding in single-stage sintering, and enabling the green body to obtain the optimal sintering driving force and diffusion mass transfer conditions in different temperature ranges.
[0027] The debinding stage (first heating stage: room temperature → 550℃~600℃, holding for 1h~2h) is the core objective of removing organic matter from the green body, including organic binders (such as polyvinyl alcohol) introduced during molding and dispersants remaining during granulation.
[0028] Mechanism of action: The organic binder undergoes a thermal oxidation decomposition reaction when heated in air. Within the temperature range of 200℃ to 500℃, the hydroxyl groups in the polyvinyl alcohol molecular chain undergo a de-oxidation reaction, causing the main chain to break and generate small organic molecules, which are further oxidized to produce CO2 and H2O gases. Controlling the heating rate (1.5℃ / min~2.5℃ / min) and setting up a sufficient heat-holding platform allows for the slow release of gases, avoiding cracking or bulging caused by a sudden increase in internal gas pressure due to rapid gas generation. Holding at this temperature for 1h~2h ensures the complete decomposition and release of organic matter, while simultaneously allowing the adsorbed water on the surface of hydrated zirconium oxide to completely desorb, providing a clean particle surface for subsequent high-temperature sintering.
[0029] The pre-sintering stage (second heating stage: 1100℃~1200℃, holding for 2h~3h) is the core objective of which is to complete the initial contact connection between zirconia particles, so that the green body can obtain a certain initial sintering strength, and to complete the pre-preparation for the crystal transformation from monoclinic to tetragonal phase.
[0030] Mechanism of action: Within this temperature range, the atomic diffusion capacity of zirconia powder particles is significantly enhanced, with surface diffusion being the primary mass transfer mechanism. Submicron-sized monoclinic zirconia particles form initial sintering necks at the contact points, and preliminary mechanical interlocking and mass migration occur between particles, leading to volume shrinkage of the green body and the acquisition of a certain processing strength. Simultaneously, the composite stabilizer (MgO, Y2O3) begins to diffuse in a solid solution reaction precursor reaction with the zirconia matrix particles at the interface, and stabilizer cations penetrate into the zirconia lattice surface, laying the compositional foundation for sufficient solid solution and crystal stabilization at high temperatures. Holding at this temperature for 2-3 hours allows the above diffusion process to proceed fully, ensuring the uniformity of the overall sintering degree of the green body.
[0031] Densification stage (third heating stage: 1450℃~1550℃, holding for 3h~5h); the core objective of this stage is to achieve a large amount of elimination of pores and significant densification of the billet through volume diffusion and grain boundary diffusion.
[0032] Mechanism of action: When the temperature rises above 1450℃, volume diffusion and grain boundary diffusion become the dominant mass transfer mechanisms in zirconia. During the mid-stage of sintering, the sintering necks between particles grow rapidly, and the interconnected pore network gradually closes into isolated pores. In this temperature range, zirconia undergoes a transformation from monoclinic to tetragonal phase. Tetragonal zirconia grains have higher symmetry and self-diffusion coefficients, significantly accelerating the volume diffusion rate. Pores migrate rapidly along grain boundaries and tend to be eliminated from the green body surface. The densification process of the green body is mainly completed in this stage, with the relative density increasing from the initial 58%~65% to over 92%~95%. Controlling a moderate heating rate (1.5℃ / min~2.5℃ / min) and sufficient holding time (3h~5h) ensures that pores have enough time to be eliminated through diffusion migration, preventing them from being "captured" by excessively closing grain boundaries and remaining as closed pores. This stage has not yet entered the rapid grain growth range, effectively densifying while avoiding premature grain coarsening.
[0033] The synergistic stage of densification and grain regulation (fourth heating stage: 1680℃~1750℃, holding for 4h~8h); the core objective of this stage is to suppress abnormal grain growth while completing the final densification, thereby obtaining a dense microstructure with fine and uniform grains. A two-stage holding process is employed: first, holding at 1680℃~1700℃ for 2h~4h, then heating to 1720℃~1750℃ and holding for 2h~4h.
[0034] Mechanism of action:
[0035] (1) Closure of residual pores (1680℃~1700℃): At a relatively low high temperature platform of 1680℃~1700℃, grain boundary diffusion is dominant. The grain boundary acts as a fast channel for pore diffusion. The remaining isolated closed pores gradually shrink and are eventually eliminated through grain boundary diffusion, and the compactness of the billet is further increased to close to the theoretical density.
[0036] (2) Uniform grain growth (1680℃~1700℃→1720℃~1750℃): The initial low temperature platform allows the grains to grow uniformly under a relatively mild driving force, avoiding abnormal local grain growth caused by a sudden temperature rise; the temperature is then slowly increased to 1720℃~1750℃, and the grains continue to grow uniformly and complete the final densification. The smaller grain size and uniform microstructure endow the material with excellent mechanical properties and thermal shock resistance.
[0037] (3) Oxygen partial pressure control (oxygen partial pressure 5%~15% throughout this stage): Zirconia is a non-stoichiometric oxide, and oxygen vacancies exist in its lattice. By controlling the oxygen partial pressure in the furnace, the concentration and migration rate of oxygen vacancies in the zirconia lattice can be controlled. An appropriate oxygen partial pressure environment (5%~15%) keeps the lattice oxygen vacancy concentration at a reasonable level, promotes lattice diffusion of cations, and accelerates the filling and elimination of pores; at the same time, the reasonable distribution of oxygen vacancies helps to suppress excessive migration of grain boundaries and avoids abnormal growth caused by individual grains rapidly engulfing surrounding small grains.
[0038] (4) Uniform distribution of stabilizers: During the long-term high-temperature heat preservation process, MgO and Y2O3 stabilizers are fully dissolved into the zirconium oxide lattice to achieve full stabilization of the tetragonal or cubic phase, preventing the volume expansion cracking caused by the martensitic phase transformation from tetragonal to monoclinic during the cooling process.
[0039] 2. By actively controlling the oxygen partial pressure in the furnace at the highest temperature, the rational distribution of oxygen vacancies in the zirconia lattice is promoted, the porosity removal and densification process is accelerated, and the abnormal growth of grains is suppressed, resulting in a microstructure with uniform grain size and dense structure.
[0040] 3. The highest temperature section of the two-stage heat preservation is set. The low temperature platform in the front section promotes the closure of residual pores, and the high temperature platform in the back section completes full sintering, which increases the bulk density of the ceramic plate to more than 5.35 g / cm³ and reduces the apparent porosity to less than 5.0%, which is significantly better than conventional single-stage sintered products.
[0041] 4. The zirconia ceramic plate prepared by the method of the present invention has significantly improved thermal shock resistance and steel slag erosion resistance, with a bulk density of 5.35 g / cm³ to 5.45 g / cm³, an apparent porosity of 2.0% to 5.0%, and a firing shrinkage rate of 12% to 16%. When used as an inlay material for converter slide plates, its service life is significantly extended and the spalling rate is significantly reduced. Detailed Implementation
[0042] The present invention will be further described in detail below with reference to the embodiments, but the scope of the present invention is not limited thereto.
[0043] Example 1
[0044] A multi-segment temperature-controlled sintering method for preparing high-density zirconia ceramic plates includes the following steps:
[0045] (1) Raw material preparation: The raw materials are fused magnesium stabilized zirconium oxide powder, monoclinic zirconium oxide ultrafine powder, and magnesium oxide stabilizer;
[0046] By mass percentage, take 60% of fused magnesium stabilized zirconia powder (D50=15μm), 35% of monoclinic zirconia ultrafine powder (D50=0.3μm), and 5% of magnesium oxide stabilizer. Add 4% of polyvinyl alcohol solution (by mass of raw materials) and 1% of deionized water (by mass of raw materials). Use zirconia balls as the grinding medium and ball mill for 6 hours to mix evenly to obtain a slurry.
[0047] (2) Granulation and molding: The slurry is granulated by a centrifugal spray granulator to obtain spherical granulated powder with a particle size of 80μm~150μm. The granulated powder is loaded into a rubber mold and isostatically pressed under a pressure of 120MPa to obtain a zirconia ceramic slab with an external dimension that meets the requirements of the converter slide plate inlay.
[0048] (3) Drying of the green body: The green body was placed in an electric heating drying oven and dried at 60°C for 4 hours, and then the temperature was raised to 110°C for 12 hours. The moisture content of the green body was measured to be 0.3%.
[0049] (4) Multi-stage temperature-controlled sintering: The dried green body is loaded into a high-temperature sintering furnace and the following sintering regime is executed:
[0050] a. Increase the temperature to 600℃ at a rate of 2℃ / min and hold for 1.5h;
[0051] b. Increase the temperature to 1150℃ at a rate of 1.5℃ / min and hold for 2.5h;
[0052] c. Increase the temperature to 1500℃ at a rate of 2℃ / min and hold for 4 hours;
[0053] d. Heat to 1700℃ at a rate of 1℃ / min and hold for 3 hours, then heat to 1730℃ at a rate of 0.5℃ / min and hold for 4 hours. During this stage, a mixture of oxygen and argon is introduced into the furnace, and the oxygen partial pressure is controlled at 8%~10%.
[0054] e. Cool to 900°C at a rate of 3°C / min, and then allow to cool naturally to room temperature in the furnace to obtain a high-density zirconia ceramic plate for converter slide.
[0055] According to the test results, the zirconia ceramic plate prepared in this embodiment has a bulk density of 5.41 g / cm³, an apparent porosity of 3.2%, and a firing shrinkage rate of 14.5%.
[0056] Example 2
[0057] A multi-segment temperature-controlled sintering method for preparing high-density zirconia ceramic plates includes the following steps:
[0058] (1) Raw material preparation: The raw materials are fused magnesium stabilized zirconium oxide powder, monoclinic zirconium oxide ultrafine powder, and magnesium oxide stabilizer;
[0059] By mass percentage, take 70% fused magnesium-stabilized zirconia powder (D50=10μm), 26% monoclinic zirconia ultrafine powder (D50=0.5μm), and 4% magnesium oxide stabilizer. Add binder and deionized water, and mix evenly by wet ball milling to obtain a slurry. Add 5% polyvinyl alcohol solution and 3% deionized water by mass of the original material. Use zirconia balls as the grinding medium and ball mill for 6 hours to mix evenly to obtain a slurry.
[0060] (2) Granulation and molding: The slurry obtained in step (1) is sprayed to granulate to obtain spherical granulated powder with a particle size of 50μm~200μm. Then the granulated powder is loaded into a mold and isostatically pressed under a pressure of 80MPa to obtain a zirconia ceramic slab.
[0061] (3) Drying the billet: Place the billet obtained in step (2) in a drying device and dry it at a temperature of 60℃~110℃ for 12h~24h to reduce the moisture content of the billet to below 0.5%;
[0062] (4) Multi-stage temperature-controlled sintering: The green body dried in step (3) is loaded into the sintering furnace and the following sintering process is performed:
[0063] a. First heating stage: Heat from room temperature to 600℃ at a rate of 1.5℃ / min, and hold at that temperature for 1h~2h;
[0064] b. Second heating stage: Heat to 1100℃ at a rate of 2.0℃ / min, and hold for 2-3 hours;
[0065] c. Third heating stage: Heat to 1450℃ at a rate of 2.5℃ / min, and hold for 3-5 hours;
[0066] d. Fourth heating stage: Heat to 1700℃ at a rate of 0.5℃ / min and hold for 3 hours, then heat to 1730℃ at a rate of 0.5℃ / min and hold for 4 hours. During this stage, a mixture of oxygen and argon is introduced into the furnace, and the oxygen partial pressure is controlled at 8%~10%.
[0067] e. Cooling section: Cool to 1000℃ at a rate of 2℃ / min, then allow to cool naturally to room temperature with the furnace to obtain a high-density zirconia ceramic plate.
[0068] The zirconia ceramic plate prepared in this embodiment has a bulk density of 5.40 g / cm³, an apparent porosity of 4.5%, and a firing shrinkage rate of 13.8%, according to the test results.
[0069] Example 3
[0070] A multi-segment temperature-controlled sintering method for preparing high-density zirconia ceramic plates includes the following steps:
[0071] (1) Raw material preparation: The raw materials are fused magnesium stabilized zirconium oxide powder, monoclinic zirconium oxide ultrafine powder, and magnesium oxide stabilizer;
[0072] By mass percentage, take 75% fused magnesium stabilized zirconia powder (D50=8μm), 20% monoclinic zirconia ultrafine powder (D50=0.6μm), and 5% magnesium oxide stabilizer. Add 5% polyvinyl alcohol solution (by mass of the raw material) and 2% deionized water (by mass of the raw material). Use zirconia balls as the grinding medium and ball mill for 6 hours to mix evenly to obtain a slurry.
[0073] (2) Granulation and molding: The slurry is sprayed to granulate to obtain granulated powder with a particle size of 100μm~200μm, and isostatically pressed at a pressure of 120MPa to obtain a green body;
[0074] (3) Drying of the billet: The billet was dried at 80℃ for 8 hours, then heated to 110℃ for 6 hours, and the moisture content was measured to be 0.4%;
[0075] (4) Multi-stage temperature-controlled sintering:
[0076] a. Increase the temperature to 580℃ at a rate of 1.8℃ / min and hold for 2 hours;
[0077] b. Increase the temperature to 1180℃ at a rate of 1.2℃ / min and hold for 2 hours;
[0078] c. Increase the temperature to 1520℃ at a rate of 2.2℃ / min and hold for 3.5h;
[0079] d. Heat to 1690℃ at a rate of 1.0℃ / min and hold for 4 hours, then heat to 1740℃ at a rate of 0.8℃ / min and hold for 3 hours, while introducing a mixture of oxygen and nitrogen gas and controlling the oxygen partial pressure to be 10%~12%;
[0080] e. Cool to 850°C at a rate of 2.5°C / min, and then allow to cool naturally to room temperature in the furnace to obtain a high-density zirconia ceramic plate for converter slide.
[0081] The zirconia ceramic plate prepared in this embodiment has a bulk density of 5.38 g / cm³, an apparent porosity of 4.1%, and a firing shrinkage rate of 13.8%, according to the test results.
[0082] Comparative Example
[0083] To verify the technical effects of this invention, green bodies were prepared using the same raw material ratio and molding process as in Example 1, and a traditional single-stage sintering process was adopted: the temperature was directly raised to 1700℃ at a rate of 3℃ / min, held for 8 hours, and then cooled in the furnace. Test results showed that the ceramic plate obtained in the comparative example had a bulk density of 5.18 g / cm³, an apparent porosity of 7.5%, and a firing shrinkage rate of 10.2%. In a converter slide test, the average service life of the comparative example product was 18 heats, while the average service life of the product in Example 1 reached 26 heats, representing an improvement of 44%.
Claims
1. A method for preparing high-density zirconia ceramic plates by multi-segment temperature-controlled sintering, characterized in that: Includes the following steps:
1. Raw material preparation: The raw materials are fused magnesium stabilized zirconia powder, monoclinic zirconia ultrafine powder, and magnesium oxide stabilizer. By mass percentage, take 60%~75% fused magnesium stabilized zirconia powder, 20%~35% monoclinic zirconia ultrafine powder, and 2%~5% magnesium oxide stabilizer, add a binder, and add 1-3% of deionized water according to the total mass of the raw materials. Use zirconia balls as the grinding medium and ball mill for 6 hours to mix evenly to obtain a slurry.
2. Granulation and molding: Spray granulation of the slurry obtained in step 1 to obtain spherical granulated powder. Then, put the granulated powder into a mold and isostatically press it under a pressure of 80MPa~120MPa to obtain a zirconia ceramic slab.
3. Green body drying: Place the green body obtained in step 2 in a drying device and dry it at a temperature of 60℃~110℃ for 12h~24h to reduce the moisture content of the green body to below 0.5%.
4. Multi-stage temperature-controlled sintering: The green body dried in step 3 is loaded into the sintering furnace and the following sintering process is performed: a. First heating stage: Increase the temperature from room temperature to 550℃~600℃ at a rate of 1.5℃ / min~2.5℃ / min, and hold for 1h~2h; b. Second heating stage: Heat to 1100℃~1200℃ at a rate of 1.0℃ / min~2.0℃ / min, and hold for 2h~3h; c. Third heating stage: Heat to 1450℃~1550℃ at a rate of 1.5℃ / min~2.5℃ / min, and hold for 3h~5h; d. Fourth heating stage: Heat to 1680℃~1750℃ at a rate of 0.5℃ / min~1.5℃ / min, hold for 4h~8h, and control the oxygen partial pressure in the furnace at 5%~15% during this stage; e. Cooling section: Cool to 800℃~1000℃ at a rate of 2℃ / min~4℃ / min, then allow to cool naturally to room temperature with the furnace to obtain a high-density zirconia ceramic plate.
2. The method for preparing a high-density zirconia ceramic plate by multi-segment temperature-controlled sintering according to claim 1, characterized in that: In step 1, the particle size D50 of the fused magnesium stabilized zirconia powder is 5μm~15μm, and the particle size D50 of the monoclinic zirconia ultrafine powder is 0.3μm~0.8μm.
3. The method for preparing a high-density zirconia ceramic plate by multi-segment temperature-controlled sintering according to claim 1, characterized in that: The slurry obtained in step 1 is spray-granulated to obtain spherical granulated powder with a particle size of 50μm~200μm.
4. The method for preparing a high-density zirconia ceramic plate by multi-segment temperature-controlled sintering according to claim 1, characterized in that: The binder mentioned in step 1 is either a polyvinyl alcohol solution or a phenolic resin, and the amount added is 3% to 6% of the total mass of the raw materials.
5. The method for preparing a high-density zirconia ceramic plate by multi-segment temperature-controlled sintering according to claim 1, characterized in that: In step 4, stage d, the oxygen partial pressure is regulated by introducing a mixture of oxygen and inert gas into the furnace, wherein the inert gas is argon or nitrogen.
6. The method for preparing a high-density zirconia ceramic plate by multi-segment temperature-controlled sintering according to claim 1, characterized in that: Step 4, stage d, adopts a two-stage heat preservation method: first, heat preservation at 1680℃~1700℃ for 2h~4h, and then heat preservation at a rate of 0.5℃ / min~1.0℃ / min to 1720℃~1750℃ for 2h~4h.
